The Relationship of Nutritional Status and Natrium Consumption Hypertension Elderly Status in the Lamongan Health Center Area - Durrotun Nihayah; Inne Soesanti; Mujayanto (Journal of Nutrition Explorations, 2023)
The elderly are vulnerable to degenerative diseases, such as hypertension. The aim of the study was to determine the relationship between nutritional status and sodium consumption with hypertension elderly status in the in the Lamongan Health Center area. Quantitative design research method with this type of observational analytic research, cross sectional study approach. A sample of 63 respondents. Sampling using accidental sampling technique. Methods of data collection by weighing and measuring body height and interviews using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) Form. The results showed that most of the elderly with hypertension were aged 60-69 years (74.6%), were female (57.1%), had a family history of hypertension (66.7%), had more nutritional status (49.2%), consumption of more sodium (54%) and hypertension status stage 1 (81.0%). The results of the Spearman correlation test stated that there was a relationship between nutritional status and hypertension status and that there was a relationship between sodium consumption and hypertension status (p=0.001;p=0.034). The conclusion of the study is that there is a relationship between nutritional status and hypertension status and sodium consumption and hypertension status in the Lamongan Health Center area. It is recommended to conduct nutrition education in the elderly.